2006
DOI: 10.1021/cm0613511
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Ni−Fe/MgO/Olivine Catalyst for Fluidized Bed Steam Gasification of Biomass

Abstract: Tar removal catalyst development is the main hurdle to improving the process of steam biomass gasification in a fluidized bed. A Ni/olivine catalyst has been previously developed to enhance the catalytic properties of calcined natural olivine and showed excellent performance and stability during biomass steam gasification in the fast internally circulating fluidized bed (FICFB) gasifier. However, the origin of its active phase was not well-understood. The present work explains the mechanism of formation and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
57
1
4

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(66 citation statements)
references
References 44 publications
4
57
1
4
Order By: Relevance
“…As a matter of fact, the sample calcined at 1100 • C did not exhibit any catalytic activity, and only data related to the Ni/dolomite sample calcined at 900 • C are shown here. Some similar tendency has been previously obtained between Ni/olivine calcined at 1100 and at 1400 • C for methane and toluene reforming [24,25].…”
Section: Catalyst Characterizationsupporting
confidence: 87%
See 1 more Smart Citation
“…As a matter of fact, the sample calcined at 1100 • C did not exhibit any catalytic activity, and only data related to the Ni/dolomite sample calcined at 900 • C are shown here. Some similar tendency has been previously obtained between Ni/olivine calcined at 1100 and at 1400 • C for methane and toluene reforming [24,25].…”
Section: Catalyst Characterizationsupporting
confidence: 87%
“…This interaction is known from previous works [24] to have beneficial effects on increasing carbon deposition resistance.…”
Section: Catalyst Characterizationmentioning
confidence: 72%
“…Before this study, the activity of calcined olivine supported nickel has been demonstrated in gasification [253] and steam reforming [254] of biomass. Olivine is a magnesium iron silicate with the general formula (Mg x Fe 1−x ) 2 SiO 4 and is a common Earth mineral.…”
Section: Nickel-iron-based Catalystsmentioning
confidence: 99%
“…It contains (Mg x Fe 1Àx ) 2-SiO 4 as the main phase and small quantities of MgSiO 3 and FeO x species [35e37]. The interactions between supported NiO and (Mg x Fe 1Àx ) 2 SiO 4 might lead to NiOeMgO solid solution formation [36], which was reported to be helpful in enhancing Ni species dispersion and stability of the Ni/olivine [36,38,39]. More importantly, the olivine could be a source of Fe for the supported bimetallic NieFe catalysts.…”
Section: Introductionmentioning
confidence: 99%